Corticosterone transfer and metabolism in the dually perfused rat placenta: effect of 11beta-hydroxysteroid dehydrogenase type 2 - Staud, F; Mazancová, K; Miksík, I; Pávek, P; Fendrich, Z; Pácha, J (Placenta, 2006)
Although rat is the most widely used model of glucocorticoid programming of the fetus, the role of rat placental 11beta-hydroxysteroid dehydrogenase type 2 (11beta-HSD2) in the transplacental pharmacokinetics of the naturally occurring glucocorticoid, corticosterone, has not yet been fully elucidated. In this study, expression of 11beta-HSD2 in the rat placenta on two different gestation days (16 and 22) was examined using quantitative RT-PCR and Western blotting, and dually perfused rat term placenta was employed to evaluate its functional capacity to transfer and metabolize corticosterone. Marked decrease in placental expression of 11beta-HSD2 toward term was observed on both mRNA and protein levels. In perfusion studies, increasing maternal corticosterone concentration from 3 to 200 nM resulted in the fall of 11beta-HSD2 conversion capacity from 64.3 to 16.3%, respectively. Enzyme saturation occurred at about 50 nM substrate concentration. When delivering corticosterone (3 or 100 nM) from the fetal side, a similar decline of 11beta-HSD2 conversion capacity was observed (66.5% and 48.5%, respectively). Addition of carbenoxolone (10 or 100 microM), a non-specific 11beta-HSD inhibitor, to maternal perfusate decreased conversion capacity from 66.7 to 12.6 or 8.1%, respectively. Similarly potent inhibitory effect was observed in feto-maternal studies. Neither saturation nor inhibition of 11beta-HSD2 was associated with transformation of corticosterone in metabolites other than 11-dehydrocorticosterone. These data suggest that 11beta-HSD2 is the principal enzyme controlling transplacental passage of corticosterone in rats and is able to eliminate corticosterone in both maternal and fetal circulations.
Keywords: karbenoxolon; Perfusion; Corticosterone; 11-beta-Hydroxysteroid Dehydrogenase Type 2; 11-beta-hydroxysteroiddehydrogenasa typ 2; Pregnancy; těhotenství; techniky in vitro; Placenta; Carbenoxolone; krysa rodu Rattus; biologický transport; placenta; Animals; kortikosteron; ženské pohlaví; zvířata; Rats; perfuze; Female; Biological Transport; In Vitro Techniques